Challenges of local authorities service delivery: a case study of Bulawayo city council (BCC) - Sibanda, Pamella (Midlands State University, 2018)
This study was carried out to evaluate the challenges of local service delivery at Bulawayo City Council. The researcher used analytical survey method which enabled the researcher to collect a lot of information regarding the study. Secondary source of available literature relating to the council was used. The researcher used random sampling; questionnaires were used to capture data from 13 residential areas. Questionnaires were distributed in 5 departments of Bulawayo Municipality to collect data. The results confirmed that there were lots of challenges faced by service seekers of Bulawayo Municipality. The challenges which mostly emanate from fatal economic doldrums caused instability that affects the success of council policies working towards improving service delivery thus curtailing the challenges thereof.